2004
DOI: 10.1272/jnms.71.172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionizing Irradiation on Human Esophageal Cancer Cell Lines by cDNA Microarray Gene Expression Analysis

Abstract: To provide new insights into the molecular mechanisms underlying the effect of irradiation on esophageal squamous cell carcinomas (ESCCs), we used a cDNA microarray screening of more than 4,000 genes with known functions to identify genes involved in the early response to ionizing irradiation. Two human ESCC cell lines, one each of well (TE-1) and poorly (TE-2) differentiated phenotypes were screened. Subconfluent cells of each phenotype were treated with single doses of 2.0 Gy or 8.0 Gy irradiations. After a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Thus, NFIL3 may block the recruitment of bZIP transcriptional activators to pro-apoptotic genes to potentially hinder chemotherapeutic response. In addition to colon cancer, NFIL3 may have a role in esophageal cancer as irradiation of esophageal cancer cell lines leads to a loss in NFIL3 expression 78 . Delineating the full breadth of NFIL3 directed transcriptional programs such as those that counter FOXO and PAR transcription factors will be essential for understanding its contribution to cancer.…”
Section: Nfil3 In Cancermentioning
confidence: 99%
“…Thus, NFIL3 may block the recruitment of bZIP transcriptional activators to pro-apoptotic genes to potentially hinder chemotherapeutic response. In addition to colon cancer, NFIL3 may have a role in esophageal cancer as irradiation of esophageal cancer cell lines leads to a loss in NFIL3 expression 78 . Delineating the full breadth of NFIL3 directed transcriptional programs such as those that counter FOXO and PAR transcription factors will be essential for understanding its contribution to cancer.…”
Section: Nfil3 In Cancermentioning
confidence: 99%
“…43 Treatment for 15 min with a single dose of 2.0 Gy or 8.0 Gy was found to induce 24 genes. 44 However, most of the genes identifi ed in these three studies do not overlap.…”
Section: Radiosensitivitymentioning
confidence: 97%
“…Disease Microarray gene expression analysis of human esophageal squamous cell carcinomas revealed that MetAP2 was down-regulated when irradiated (Bo et al, 2004).…”
Section: Esophageal Squamous Carcinomamentioning
confidence: 99%
“…The Src family kinases have been shown to play pivotal roles in cell-cycle progression, making them potential candidates to mediate the cell-cycle effects of MetAP inhibitors. MetAP2 plays a critical role in the proliferation of endothelial cells and certain tumor cells and thus serves as a promising target for antiangiogenesis and anti-cancer drugs (Bo et al, 2004). The inhibition of MetAP2 expression in mesothelioma cells leads to cell death and that such apoptosis is avoided in cases where there is overexpression of Bcl-2 (Catalano et al, 2001).…”
Section: Metap2 Inhibitorsmentioning
confidence: 99%